Status of Research and Improvement Efforts of Alcohol Patchouli Content In Oil Patchouli - SETIAWAN .; ROSIHAN ROSMAN (Puslitbang Perkebunan, 2013)
Patchouli (Pogostemon cablin Benth.) as the oil-producing plant is known through patchouli oil. Patchouli oil is one of natural ingredient that has a very important role in the industry of cosmetics and perfumes. Patchoulol (patchouli alcohol/PA) is the most important compound which secretes aroma and are often used as an indicator of the quality of patchouli oil. But this time, the PA content of Indonesian patchouli oil mostly <31%, whereas the ISO standard requires over 31%. Therefor, efforts to increase the patcouli alcohol content is higher indispensable either through improved crop and post harvest. Various studies have been conducted from land suitability and climate, varieties and post-harvest. The results showed that the content of PA can be improved more than 50% Key words : Patchouli, patchouli alcohol, technology, improvements